PENGARUH PENGGUNAAN HYPNOTEACHING PADA PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR SISWA KELAS VII SMPN 2 UTAN TAHUN PELAJARAN 2015/2016 - Aminah, Siti; Nissa, Ita Chairun; Juliangkary, Eliska (Universitas Pendidikan Mandalika (UNDIKMA), 2017)
This study aims to determine the effect of using hypnoteaching on problem based learning toward the students learning outcomes at VII grade studen of SMPN 2 Utan. The Type of research is a eksperimental research. The population of this research includes all students of class VII SMPN 2 Utan. The sampling technique used purposive sampling. The class VII2 as the experimental class Â and class VII 4 as the control class. The data collection is done by using about pre-test and post-test form. Data processing is done by statistical analysis. The results showed that t_count = 2.17 is greater than t_table = 2.001. so it can be concluded that the hypothesis is rejected Ho and Ha accepted. That Â means that the treatment given to the experimental group have an influence towars the student learning outcomes using model hypnoteaching on problem based learning at VII grade student of SMPN 2 Utan